Corpus of perfume and cosmetic goods names and its parameters - Nikiforova , Yevhenia; Popivniak , Olena; Galitska, Elizaveta (Current issues of Ukrainian linguistics: theory and practice, 2022)
The article deals with the perfume and cosmetic name corpus research in the aspect of parametrization in multiaspective and multistructural ways. Multiaspective peculiarities are divided into naming and informational aspects. Multistructural features are reflected in the combination of A-brand (manufacturer), B-basic (individual), C-genitive (article), D-functional-descriptive integrants. The next level of multistructural features is connected with the combination of integrants into bigger structures, they are integrators. They are associated within the huge article unit name corpus. The corpus itself consists of such semantic components as quantificators, qualificators, determinatives. Naming integrator corpus provides the discrimination of article units, and demonstrates the involvement of naming devices and some shade of social stratification. Involvement of naming register is reflected in the corpus too. Article units are associated with their naming integrators. In the process of research there were two stages of selection. The primary stage identified 54 classes of goods. The secondary one identified 13 leading classes of olfactory and colouring goods. Parameters which are identified in the process of parametrization may be qualitative and quantitative in their mutual functioning and correlation. Quality and quantity are reflected in goods types, naming devices, naming register. The goods name corpus is a stock of information, knowledge about article units. The informational nucleus is created with two subgroups. The first subgroup represents some information about olfactory, aroma, fragrance, odour. The second one contains some information about optical effect, colouring, tinting, masking.